Manfaat Manfaat Membaca Dongeng Sebelum Tidur terhadap Minat membaca Anak - Nurul Aulia (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Reading fairy tales before bedtime is a simple activity that can help improve children's interest in reading. This study aims to examine the benefits of bedtime storytelling for children's reading motivation and literacy development. The research used a descriptive qualitative method with a literature review approach. Data were collected from journals, books, and academic articles found through Google Scholar and analyzed using thematic content analysis.The results show that bedtime storytelling can be implemented through regular parent-child reading activities and discussions about story content. This practice helps children improve vocabulary, comprehension, imagination, and communication skills. It also encourages positive attitudes toward books and reading. In addition, stories introduce children to social values and cultural knowledge that support their personal development.In conclusion, reading fairy tales before bedtime is an effective way to foster reading interest and strengthen literacy skills. Regular storytelling activities can help children become more motivated readers and support their overall language development.